Microplastic Content in the Stomach of Caru Fish (Megalaspis cordyla) in the Sea Waters of Dumai City, Riau Province - Saputra, Eka; Nasution, Syafruddin; Yoswaty, Dessy (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Microplastics are particles that have a size of <5 mm and their existence might be able to contaminate the biota in the aquatic environment, such as care fish. Caru fish was collected in the Dumai city fish landing base in September - December 2022 to determine the abundance of microplastics in caru fish. The method used in this study is a survey method; samples of caru fish were obtained from Fish Landing Base (PPI) Dumai, and the samples were analyzed for the microplastic content in the laboratory. The samples used were 90 caru fish divided into three size classes. The parameters measured included type of microplastic, microplastic abundance, microplastic colour and the relationship between care fish size and microplastic abundance. The abundance of microplastics from the three size class of fish shows that the size class 22.1-24 cm had a higher average abundance of microplastics with an average value of 5.7 particles/individual. The type of microplastics found in this study were fibre, film and fragment. The relationship between the length of the caru fish and the abundance of microplastics has not been influenced by the size of the carp fish.